anonymous
  • anonymous
Use the elimination method to solve the following system of equations. 4x – 2y – z = –5 x – 3y + 2z = 3 3x + y – 2z = –5
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
texaschic101
  • texaschic101
4x - 2y - z = -5 x - 3y + 2z = 3 -->(-4) --------------- 4x - 2y - z = - 5 (result of multiplying by -4) -4x + 12y - 8z = - 12 ----------------add first two equations 10y - 9z = - 17 x - 3y + 2z = 3 -->(-3) 3x + y - 2z = - 5 --------------- -3x + 9y - 6z = - 9 (result of multiplying by -3) 3x + y - 2z = - 5 ----------------add last two equations 10y - 8z = - 14 now add the answers of both sets of equations... 10y - 9z = - 17 -->(-1) 10y - 8z = - 14 -------------- -10y + 9z = 17 (result of multiplying by -1) 10y - 8z = - 14 ---------------add z = 3 Now sub 3 in for z in either of the above equations... 10y - 8z = - 14 10y - 8(3) = - 14 10y - 24 = - 14 10y = - 14 + 24 10y = 10 y = 1 now sub 1 in for y and 3 in for z in any of the first 3 equations 4x - 2y - z = - 5 4x - 2(1) - 3 = - 5 4x - 2 - 3 = - 5 4x = - 5 + 5 4x = 0 x = 0 Now sub all 3 known variables into any of the first 3 equations to check your answers... x - 3y + 2z = 3 0 - 3(1) + 2(3) = 3 -3 + 6 = 3 3 = 3 (correct) ANSWER : (0,1,3) <--- x = 0, y = 1, z = 3 :)
anonymous
  • anonymous
Thank you so much for putting your time into helping me!
texaschic101
  • texaschic101
Not a problem...thats what I am here for :)

Looking for something else?

Not the answer you are looking for? Search for more explanations.